Peran Zakat sebagai Jaring Pengaman Sosial di Tengah Masa Darurat Bencana Covid-19 pada BAZNAS Kota Palembang - Dian Pitaloka; Istiani Khasanatun; Diva Anggraini; Ali Maftuhin; Maya Panorama (QULUBANA: Jurnal Manajemen Dakwah, 2022)
The COVID-19 outbreak poses a major risk to the economy of Palembang, causing social inequality in the community. In this case, the role of zakat as a social safety net is indispensable. BAZNAS acts as a forum for distributing zakat muzakki. The government established BAZNAS under the Ministry of Religious Affairs. BAZNAS was established in 2001 by Presidential Decree No. 8 of the Republic of Indonesia to implement Law No. 38 of 1999. Zakat can be a solution to optimize people's finances during a pandemic, so zakat as a social safety net plays a very important role in improving people's finances.